Analisis Rasio Keuangan untuk Memprediksi Kondisi Financial Distress pada Perusahaan Perkebunan Kelapa Sawit yang Terdaftar di Bursa Efek Indonesia - Sibarani, Rosmei Yunita (Jurnal Manajemen dan Ilmu Administrasi, 2025)
This research uses secondary data from annual financial report of plantation sub sector companies in Indonesia Stock Exchange. Researcher using purposive sampling in order to obtain a sample of 10 companies. The decline of crude palm oil commodity prices and world demand in 2014 to 2016 lead to decline the capability of plantation companies performance. This is apparent from the declining sales capacity, increase of operating expenses, and inventory expenses and the impact is declining financial performance such as net profit. If this is allowed continuously then the consequences are the plantation sub sector companies possibly can get into the financial distress condition. This research aims to predict the level of financial distress condition and to know the relationship significance using Return On Asset (ROA), Return On Equity (ROE), Current ratio (CR), Debt to Asset Ratio (DAR), Current Liabilities to Assets Ratio (CLAR) and Debt to Equity Ratio (DER). The research population was plantation sub sector companies listed in Indonesia Stock Exchange. Data were tested using logistic regression to explain the influence between these variables. The results of this research indicate that the Return On Equity (ROE), Current ratio (CR), Debt to Asset Ratio (DAR), and Debt to Equity Ratio (DER) did not significantly influence financial distress while Return On Asset (ROA), Current Liabilities to Assets Ratio (CLAR) significantly influence financial distress.